ВЛИЯНИЕ ГИПЕРГЕННЫХ УСЛОВИЙ НА КАЧЕСТВО ИСКОПАЕМОЙ МАМОНТОВОЙ КОСТИ - Смирнов A.H. (My University, 2006)
Fossil ivory (FI) - tusks of Siberian mammoth (Mammuthus primigenius) - is a complicated organic-mineral aggregate of orthobiogenic origin. As a natural composite, it consists of collogene, water and hydroxylapatite (up to 50 %). The paper briefly considers features of composition and structure of the mammoth tusk; its elementary composition was studied by microprobe analysis: CaO 18.30-25.94%, P2O5 14.93-21.55%, MgO 0.23-1.82 % (CamScan MV 2300, OXVORT, LINK ISIS-300). There is also shown influence of taphonomic settings on the qualitative characteristics of FI, i. e. its commercial value.
Keywords: 551.311.22:569.61